In Vivo Macroscopic Study of Ziziphus jujuba Extract Ointment in Accelerated Burn Wound Healing in Rats - Davina Taniago; Suandy Suandy; Rudi Chandra (Green Publisher Indonesia, 2025)
Burns are type of injury that damage the skin which caused by exposure to heat sources that requiring comprehensive management and potentially leading to high morbidity. Limited resources and costs often encourage the use of herbal ingridients as an alternative. Ziziphus jujuba (Chinese date) has been traditionally used in Chinese medicine (TCM) for its healing property. Ziziphus jujuba contains various bioactive compounds such as flavonoids, saponins, and tannins that contribute to wound healing through their anti-inflammatory, antioxidant and regenerative mechanisms. This study aims to test the effectiveness of Ziziphus jujuba extract ointment on burn wound healing in Rattus norvegicus. Ointment preparations were made in concentrations of 10 mg/mL and 20 mg/mL, then tested physically (organoleptic, homogeneity, pH, spreadability). This study used a trueexperimental method with a post-test only control group design, involving four treatment groups, each consisting of six rats with back burns: control (K), MEBO as control positive (P1), 10 mg/mL Ziziphus jujuba extract ointment (P2), and 20 mg/mL Ziziphus jujuba extract ointment (P3). The study was conducted 21-day obervation period to evaluate wound diameter, wound healing percentage, macroscopic and microscopic assesment based on the modified Nagaoka criteria. The group treated with Ziziphus jujuba ointment 20 mg/mL (P3) achieved the best healing outcomes, chracterized by faster wound reduction, minimal adverse local and allergic reactions, and shorter healing period than those observed in the control and other treatment groups.